Project-based Learning: Changing Students' Scientific Thinking to Be Creative from Waste Natural Materials - Pamella Mercy Papilaya; John Rafafy Batlolona; Sefnath Nuniary; Marleny Leasa (Jurnal Penelitian Pendidikan IPA, 2023)
The main objective of this study is to analyze students' scientific creativity in each domain with an essay test referring to the Torrance Tests of Creative Thinking. This research was conducted on 50 teachers and 500 students in 10 elementary schools in Cluster 2, Nusaniwe District, Ambon City. The results of this study report descriptive demographic results of respondents and the level of creativity, namely fluency, flexibility, originality and elaboration among students is very good. The results of the study as a whole show that most of the students are at a good level after being taught with the PjBL model. Students increase their creativity with the teacher's instructions and directions. Initially in detail, many students lack the dimensions of fluency, flexibility, originality and elaboration so they cannot provide more ideas, and cannot provide answers. So that the originality becomes less and they have no ideas to elaborate further than the answers given. However, based on the findings from several student meetings, there has been a significant increase. This is because it applies a problem-oriented learning model that enhances each realm of creativity in science subjects. In addition, the researcher also recommends conducting more in-depth research on creative thinking processes among students based on the local advantages of each school based on geographical location which has its own unique value. Therefore, teachers are expected to be able to better understand cognitively, affectively and psychomotor in students' minds and possibly improve students' creative thinking skills on each dimension of creativity